Descrição dos machos de Eufriesea nigrohirta (Friese, 1899) (Hymenoptera: Apidae) com comentários sobre o holótipo, a biologia da espécie e distribuição (Lundiana: International Journal of Biodiversity, 2005)
Eufriesea nigrohirta (Friese, 1899) was described based on a single female from Pará state, northern Brazil. However, no more specimens have ever been collected in northern Brazil, but several specimens which have often been attributed to this species have been collected above 1,000-m elevation in the “campos rupestres” of mountain ranges in Minas Gerais and Bahia states. A comparison of these females to the holotype of E. nigrohirta has shown that they belong, in fact, to this species. The male is described for the first time. A list of all plant species known to be visited by E. nigrohirta is also presented.